Evolution of disease mortality burden in Cuba: 1990-2005 - Seuc,Armando H. (2010)
The objective of this study was to estimate the evolution of the burden of disease in Cuba for 20 major causes at five year intervals from 1990 to 2005, in terms of mortality and years of life lost due to premature death (YLL), using national mortality registries. Six summary measures were computed for each of the 20 major causes of death which characterized the evolution of the disease burden over the period studied. The 20 causes were then grouped according to their behaviour in these summary measures; hierarchical cluster analysis was used to support this grouping process. We compute YLL results with and without age-weighting and time discounting (3%). The 20 major causes were grouped into 12 subgroups, each with a particular pattern. The burden of disease in Cuba during the period 1990-2005 has a peculiar pattern that does not reproduce the one characteristic of other low- and middle-income countries. The approach used in this study supports a better description of mortality and YLL trends for major causes, for identifying possible explanations, and for supporting public health policy making. It seems convenient to reproduce this analysis using shorter time intervals, e.g. annually.